Reclaiming colonial architecture - Sengupta, Tania; King, Stuart (London : RIBA Publishing, 2024)
Offering historical background, unpacking key concepts and presenting thematically organised and multi-scalar urban and architectural case studies, this accessible text showcases how legacies of colonialism are being dealt with. Case studies highlight actions by built environment professionals such as architects and heritage practitioners, as well as community initiatives and activism. The book aims to build confidence in practitioners, students and communities grappling with a seemingly vast and complex terrain of debates and approaches around colonial landscapes, urban areas, buildings, monuments and material culture. A helpful resource for architecture schools or critical heritage studies departments/organisations, the book will offer a point of departure for graduate student inquiry and its accessible nature will help introduce undergraduates to concepts of colonial built-environments.
Keywords: Architecture, Colonial; ARCHITECTURE / Criticism